The Synergistic Effects of Self-Regulation Tools and the Flipped Classroom. Issue 1 (2nd January 2016) - Butzler, Kelly B.
ABSTRACT: Students at open-enrollment institutions enter college with a wide range of academic preparedness and are often required to take developmental classes to increase their academic skills to be successful in higher education. Further, few students possess self-regulated learning skills to aid in their learning. Researchers posited that academically at-risk students benefit from gains in self-regulated learning skills when a modeling and scaffolding approach is used to implement self-regulated learning tools. Self-regulated skills coupled with an active learning environment like the flipped classroom provide positive synergistic effects for academically at-risk students. This study compared several iterations of the flipped classroom in a general chemistry class at an open-enrollment college where high school class rank and mathematics placement level varied significantly. The results of the multiple regression analysis indicated that mathematics level and class rank were significant when predicting overall course grade regardless of the learning environment. The results of a paired-samples t test did not reveal a significant difference upon addition of note-taking and exam wrappers in a flipped classroom learning environment. However, students graduating high school in the top third, middle third, and bottom third of their graduating class increased their overall course grades in a flipped classroom using self-regulated tools by 7%, 3%, and 6%, respectively. To enhance the quantitative results, the author provides student comments on note-taking and the use of exam wrappers.